Identification “Merdeka Curriculum” of Elementary School Levels in Tomohon City - Mamuaja, Marlin Penina; Katuuk, Deitje Adolfien; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (JR Education, 2023)
The